(untitled) (Research, Society and Development, 2021)
Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHS) is the most common sleep disorder in the population and is characterized by five or more episodes of partial or total upper airway (UA) obstruction during sleep, for a period equal to or greater than 10 seconds. The most common reported symptoms are daytime sleepiness, night snoring, restless sleep and excessive fatigue, which directly interfere at the individual’s quality of life. This work aims to approach orthognathic surgery as a treatment option for Obstructive Sleep Apnea-Hypopnea Syndrome. It is a literature review where it was performed a search related to the topic covered at the databases SCIELO (Scientific Electronic Library On-line), PubMed, Science Direct and Google Scholar, in the period from 2013 to 2020. OSAHS is a serious public health problem, and it is also up to the dental surgeon to diagnose and treat, being the advancement maxillomandibular orthognathic surgery a safe and effective alternative.